Studies on Monstereae (Araceae) of Borneo III — Two new Rhaphidophora species with perforated leaf blades - Wong, Sin Yeng; Boyce, Peter C. (International Aroid Society, 2022)
Two new species of Rhaphidophora with perforated leaf blades are described from Borneo and illustrated from living plants. An identification key to the five morphologically similar Bornean species is provided.